2020
DOI: 10.1002/csc2.20027
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of total lipid production in vegetative tissues of alfalfa and sainfoin using chemical mutagenesis

Abstract: Alfalfa (Medicago sativa L.) and sainfoin (Onobrychis viciifoila Scop.) are two key forage legumes for the western Canadian cattle industry. Despite the high protein content, drawbacks to their use exist, including inefficient protein digestibility and energy use efficiency in the ruminant system, leading to economic losses and negative environmental impacts. Increasing the proportion of lipids in the diet of cattle is known to mitigate greenhouse gas emissions; however, the above two forage legumes possess on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
2
11
0
1
Order By: Relevance
“…Plants exhibiting substantial reductions in target transcript levels based on qRT‐PCR analysis were tested for lipid content using near‐infrared (NIR) spectrometry (Foss NIR systems 6500) as described previously (Wijekoon et al., 2020). This approach is typically used for measuring forage quality parameters including protein, fat, dry matter, and crude fiber and has been used previously to assess foliar oil characteristics in a Melaleuca cajuputi Powell breeding population (Schimleck, Doran, & Rimbawanto, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants exhibiting substantial reductions in target transcript levels based on qRT‐PCR analysis were tested for lipid content using near‐infrared (NIR) spectrometry (Foss NIR systems 6500) as described previously (Wijekoon et al., 2020). This approach is typically used for measuring forage quality parameters including protein, fat, dry matter, and crude fiber and has been used previously to assess foliar oil characteristics in a Melaleuca cajuputi Powell breeding population (Schimleck, Doran, & Rimbawanto, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…In forage species such as alfalfa, leaf tissues produce an abundance of polar lipids for the production of cell membranes, with a total lipid content of ∼3% of dry matter (Barrett et al., 2015), and there appears to be little genetic variation in this trait. As such, little progress has been made using conventional breeding approaches to increase the lipid content of vegetative tissues in forages (Glasser, Doreau, Maxin, & Baumont, 2013; Hegarty et al., 2013; Palladino et al., 2009; Wijekoon et al., 2020). Furthermore, although the alfalfa genome has been sequenced and assembled at the diploid level (http://www.alfalfatoolbox.org/doblast), such information is not available at the tetraploid level and functional genomics applications have thus been limited in this species (Biazzi et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the lipid content in the diet of cattle is known to mitigate greenhouse gas emissions and the supplementing feed with moderate amounts of oil reduces methane production by ruminants (Bayat et al, 2018;Singer et al, 2018). Limited research is available on profiling fatty acids in sainfoin (seed and vegetative tissue) (Tarasenko et al, 2015;Wijekoon et al, 2020), and further research is needed full characterization of the lipophilic fraction. The lipid fraction of fenugreek seeds revealed that oleic acid (C18:1), linoleic acid (C18:2), and α-linolenic acid (C18:3) are the main fatty acids present, but myristic acid (C14:0), pentadecylic acid (C15:0), palmitic acid (C16:0), margaric acid (C17:0), stearic acid (C18:0), arachidic acid (C20:0), eicosenoic acid (C20:1), and behenic acid (C22:0) were present in lower quantities (Chatterjee, Variyar, & Sharma, 2010, Bienkowski, Zuk-Golaszewska, Kaliniewicz, & Golaszewski, 2017Rathore et al, 2017).…”
Section: Crop Sciencementioning
confidence: 99%
“…The digestion rate of sainfoin is initially lower than that of alfalfa, showing its bloat-safe characteristics (Coulman et al, 2000). A few studies have shown the involvement of sainfoin in reducing lethal bloat in cattle (Acharya et al, 2013;de la Iglesia, Milagro, Campión, Boque, & Martínez, 2010;Huyen et al, 2016;Wang, Berg, Barbieri, Veira, & McAllister, 2006a, 2006bWijekoon et al, 2020). It has…”
Section: Benefits Of Sainfoin and Fenugreek As A Forage Crop For Farmmentioning
confidence: 99%
See 1 more Smart Citation